Molecular origins of wettability of hydrophobic poly(vinylidene fluoride) microporous membranes on poly(vinyl alcohol) adsorption: Surface and interface analysis by XPS - Gholap, S. G.; Badiger, Manohar V.; Gopinath, Chinnakonda S. (Journal of Physical Chemistry B, 2005)
irreversible adsorption of poly(vinyl alcohol) (PVA) on hydrophobic, porous poly(vinylidene fluoride) (PVDF) membranes was carried out using aqueous PVA solution. Water permeation was observed in PVDF microporous membranes after PVA adsorption, and maximum permeability was obtained after treatment with 4% PVA solution. Water permeability increased linearly with increasing PVA concentration up to 4%, and then a marginal decrease with a further increase in PVA concentration occurred. PVA adsorbed PVDF membranes were subjected to intense physicochemical analysis, especially with XPS. XPS results display the presence of an interface between PVA and PVDF, and the binding energy (BE) of the interface is low for the PVDF membranes treated with 4% PVA. Carbon from CF2-groups and F 1s core level clearly showed a decrease in its content on the surface after PVA adsorption and showed a minimum fluorine content at 4% PVA. F Is BE shifts by 0.5 eV upon PVA adsorption and is independent of PVA concentration. EDAX analysis indicates that the bulk oxygen content remains within 4.5 +/- 0.6% and is independent of the PVA concentration. Nonetheless, a large amount of surface atom percentage of oxygen (20 +/- 4%) from 0 Is core level shows an increase in PVA content on the surface of PVDF, and it is restricted mostly to the surface. The 4% PVA treated PVDF membrane clearly shows a broadening of O 1s core level to lower BE and indicates the interaction between PVDF and PVA which is significantly different compared to any other compositions. A new valence band feature at low BE, which is nonexistent on PVDF, develops after PVA adsorption. This indicates that the shift in the nature of the highest occupied molecular orbital (HOMO) derived mostly from oxygen; simultaneously, a suppression in the PVDF derived band indicates the change in nature of the PVA adsorbed surfaces from hydrophobic to hydrophilic. The above observations also suggest an irreversible electronic interaction between PVA and PVDF, possibly through charge transfer.